Análise shift share: um estudo comparativo da produção cacaueira nos estados da Bahia e do Pará no período de 1996-2016 - Costa, Ana Grasielle Nervino (2019)
The cocoa economy in Brazil since the 1990s has undergone changes mainly in its largest producing state, Bahia, which was devastated by the witch-broom associated with climatic conditions and those inherent in the cocoa market. However, the state of Pará is on a growing and different trajectory, currently occupying the second place in the national ranking. The objective of this study is to compare the cocoa economies in the states of Bahia and Pará in order to identify which factors were responsible for the growth or decrease of production. Searching through the shift share model compare if there was change in the structural component for the variable cocoa production for the two regions. The analysis was applied comparatively to the main producing regions of the country, Bahia located in the northeast region and Pará in the northern region of the country. He highlighted the main municipalities producing each state to decompose the growth of cocoa production in the effects area, income effect and geographic location effect. The data used in the analysis were from the Municipal Agricultural Production of the IBGE in the periods 1996 / 2016. It was concluded that the growth of production in the state of Pará was positively associated with the effects area and yield, but a need for verticalization would be fundamental for the strengthening of the productive chain of cocoa. The state of Bahia presented negative rates of production growth affected by the effects of area and yield, however the existence of an industrial pole formed by cocoa processors still put it ahead of the state of Pará when considering the geographic location effect.